Analysis of State Fund Placement of IDR 200 Trillion in Partner Banks: A Review of Protection of Assets (Ḥifẓ Al-Māl) From the Perspective of Maqāṣid Al-Shariah - Fadilla Ramadania Adissifa; Munawar Hakimi Ahmad Qulyubi; Dwi Suci Widiastuti; gyassurahAhmad Giyas Surahman; Tiara Indah Meygantari (Jurnal Ilmiah Global Education, 2026)
The placement of IDR 200 trillion in state funds in partner banks constitutes a strategic government cash management instrument to maintain fiscal liquidity and strengthen banking intermediation. As it involves public wealth, this policy must be evaluated from the perspective of asset protection (ḥifẓ al-māl) within the framework of maqāṣid al-sharī‘ah. This study aims to assess the compatibility of the policy with the principle of ḥifẓ al-māl through an analysis of policy design, implementation, and associated governance risks. This research employs a qualitative descriptive approach based on document analysis of fiscal regulations, supervisory authority reports, and relevant academic literature. The findings indicate that the policy is effective in maintaining nominal fund security and short-term banking stability; however, significant weaknesses remain in terms of transparency, accountability, and the optimization of social benefits. Therefore, strengthening the orientation toward public welfare is an urgent necessity in managing state funds.